2018
DOI: 10.1007/s10803-018-3508-y
|View full text |Cite
|
Sign up to set email alerts
|

Superior Disembedding in Children with ASD: New Tests Using Abstract, Meaningful, and 3D Contexts

Abstract: Since its initial development, the embedded figures test (EFT) has been used extensively to measure local–global perceptual style. However, little is known about the perceptual factors that influence target detection. The current study aimed to investigate disembedding in children with and without ASD, aged 8–15 years, using the newly developed, stimulus-controlled L-EFT, M-EFT and D-EFT. Firstly, results revealed superior disembedding for children with ASD, irrespective of the type of target or embedding cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 52 publications
(71 reference statements)
0
14
0
Order By: Relevance
“…Importantly, no visual task assesses global or local processing in isolation from other abilities, and alterations in executive functions commonly found in ASD (Lai et al., ) might affect performance in these tasks. Further, the tasks used here were not designed to investigate the impact of low‐level stimuli features which have previously been shown to modulate performance in relation with ASD and autistic traits (Bertone, Mottron, Jelenic, & Faubert, ; Van der Hallen, Chamberlain, de‐Wit, & Wagemans, ) and do not allow conclusions whether observed differences are related to lower or higher level visual processing (Grinter et al., ; Pellicano, Gibson, Maybery, Durkin, & Badcock, ). Future twin studies should address these gaps by using tasks systematically manipulating features, such as the amount of target lines continuing into the context in the EFT (Van der Hallen et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, no visual task assesses global or local processing in isolation from other abilities, and alterations in executive functions commonly found in ASD (Lai et al., ) might affect performance in these tasks. Further, the tasks used here were not designed to investigate the impact of low‐level stimuli features which have previously been shown to modulate performance in relation with ASD and autistic traits (Bertone, Mottron, Jelenic, & Faubert, ; Van der Hallen, Chamberlain, de‐Wit, & Wagemans, ) and do not allow conclusions whether observed differences are related to lower or higher level visual processing (Grinter et al., ; Pellicano, Gibson, Maybery, Durkin, & Badcock, ). Future twin studies should address these gaps by using tasks systematically manipulating features, such as the amount of target lines continuing into the context in the EFT (Van der Hallen et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…In the EFT, participants must locate a simple target shape within a complex stimulus. When a target is embedded within a context, it becomes hidden because of shared lines, overlapping colors, and distracting patterns (De‐Wit, Huygelier, Van der Hallen, Chamberlain, & Wagemans, ; Poirel, Pineau, Jobard, & Mellet, ; Van der Hallen, Chamberlain, De‐Wit, & Wagemans, ). This contrasts with visual search paradigms where a target is surrounded by distractor elements but is not embedded within a context (Wolfe & Horowitz, ) and matching tasks where a target shape has to be identified among a number of distinct, nonoverlapping choices (Li, Wu, Zhu, & O'Boyle, ).…”
Section: Measures Of Fimentioning
confidence: 99%
“…This has resulted in a lack of clarity about what FI represents (Evans, Richardson, & Waring, ). The literature sometimes describes FI in perceptual terms, where success is related to overcoming the Gestalt principles of proximity, similarity, and good continuation (De‐Wit et al, ; Van der Hallen et al, ). However, it is also described in cognitive terms, as the extent to which individuals are able to analyze and restructure a given stimulus to solve a problem that requires details to be decontextualized (Pithers, ; Rémy & Gilles, ; Witkin, Moore, Goodenough, & Cox, ).…”
Section: Measures Of Fimentioning
confidence: 99%
“…13 Studies also confirmed that higher autistic traits were associated with superior visual perceptual skills 14 and search skills. 15 In addition, Stotesbury et al 16 reported that individuals with higher schizotypal traits had greater performance decrements of attentional function when they needed to pay attention to lots of stimuli. Researchers also found that sustained attentional deficits were associated with individuals of higher schizotypal traits.…”
Section: Introductionmentioning
confidence: 99%